2004
DOI: 10.1007/s00253-004-1728-x
|View full text |Cite
|
Sign up to set email alerts
|

Robust NADH-regenerator: improved ?-haloketone-resistant formate dehydrogenase

Abstract: Formate dehydrogenases (FDH) are useful for the regeneration of NADH, which is required for asymmetric reduction by several dehydrogenases and reductases. FDHs have relatively low activity and are labile, especially to alpha-haloketones, thus FDH cannot be applied to the industrial manufacture of optically active alpha-haloalcohols. To stabilize a FDH from Mycobacterium vaccae (McFDH) against the alpha-haloketone ethyl 4-chloroacetoacetate (ECAA), a set of cysteine-mutant enzymes was constructed. Sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 27 publications
0
34
0
1
Order By: Relevance
“…In addition, the electrochemical reduction of CO 2 to formate has been described [8], suggesting a suitable model not only for producing formate for biofuel applications, but also for using the accumulating greenhouse gas CO 2 in the atmosphere. The main problems in working with most FDHs published so far are protein instability, sensitivity to oxygen, and low turnover rates [28][29][30]. In addition, most FDHs, like those studied in E. coli, require toxic selenium in their active sites, hindering large-scale protein expression, and the oxygen sensitivity of the proteins necessitates purification under anaerobic conditions [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the electrochemical reduction of CO 2 to formate has been described [8], suggesting a suitable model not only for producing formate for biofuel applications, but also for using the accumulating greenhouse gas CO 2 in the atmosphere. The main problems in working with most FDHs published so far are protein instability, sensitivity to oxygen, and low turnover rates [28][29][30]. In addition, most FDHs, like those studied in E. coli, require toxic selenium in their active sites, hindering large-scale protein expression, and the oxygen sensitivity of the proteins necessitates purification under anaerobic conditions [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…For the biocatalytic approach, the following systems were employed: (i) isolated alcohol dehydrogenases (e.g., from Rhodococcus erythropolis, [12] bakers yeast, [13 -15] horse liver, Thermoanaerobium brockii, Lactobacillus brevis, [16] or Pseudomonas sp. [17] ), (ii) E. coli transformants expressing a carbonyl reductase (e.g., from Candida magnoliae, [18,19] ) or an alcohol dehydrogenase (e.g., from Candida parapsilosis [20] or Kluyveromyces aestuarii [21] ) as well as (iii) whole cells (preferentially yeast [5,7,22 -25] , Geotrichum candidum [2,5,26 -28] or various strains [9,22,26,29 -32] ). One reason for the high significance of chiral a-halohydrins is their broad applicability as chiral intermediates, e.g,.…”
Section: Introductionmentioning
confidence: 99%
“…The number of cysteines contained in FDHs from different sources varies between two and nine per subunit. In previous studies, it has been demonstrated that site-directed mutagenesis of cysteine residues enhances the stability of FDHs toward oxidative stress and reactive compounds like α-haloketones (Slusarczyk et al 2000;Tishkov et al 1993;Yamamoto et al 2005). The identification and development of FDHs with high resistance to α-haloketones is of commercial interest since α-haloalcohols (halohydrins) are important building blocks for organic syntheses.…”
mentioning
confidence: 99%
“…Each subunit of MycFDH contains seven cysteine residues. In particular, C145 and C255 have been demonstrated to have a major impact on the chemical stability of the enzyme (Yamamoto et al 2005). C145 is adjacent to N146, which is involved in the binding of formate, whereas C255 is located in the cofactor-binding pocket and interacts with the adenine moiety of NAD + .…”
mentioning
confidence: 99%